(untitled) (International Conference on Computers in Education, 2019)
This work-in-progress study used online community-based flipped learning platform to explore college students’ learning motivation in the oral presentation. A sample of 95 college students studying English as a foreign language (EFL) was assigned into control and experimental groups, with 40 and 55 students in each group based on a pre-test. Both groups were further divided into groups of two or three students for their oral presentation. Data collection consisted of pre- and post-tests and evaluations of group project presentations. Both groups uploaded their group projects with images to the online learning platform, and then gave a brief presentation of their final project. Students’ group projects were evaluated by three teachers. The difference between control and experimental groups is the latter group recorded the video-mediated oral feedback to provide comments for other teams’ oral presentation besides recording their oral presentation videos with written feedback. The results of this study indicated that the students in the experimental group perceived their learning process in oral presentation positively and performed better than those of the students in the control group. They provided positive and immediate feedback to their peers and clearly perceived peers’ annotations which enhanced oral presentation in terms of pronunciation, fluency, comprehension, and relevance of the content. This study suggests EFL college students to use online community-based flipping learning to raise their learning motivation for the oral presentation.